Application of Compensation Money Legal Sanctions in Corruption Crimes in Indonesia and the United States - Rr. Dijan Widijowati (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
After the issuance of TAP MPR Number IX/MPR/1998 concerning State Administration that is Clean and Free from Corruption, Collusion and Nepotism, the People's Representative Council of the Republic of Indonesia (DPR RI) then issued a series of laws against corruption, including: Law Number 31 of 1999 concerning the Eradication of Corruption Crimes; and Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. Apart from that, the government is also making efforts through determining the payment of money as compensation for corruption. The problem is how is the legal comparison between Indonesia and the United States regarding criminal sanctions for money as compensation in the concept of law enforcement on corruption crimes? The research used is normative legal research, namely a scientific research procedure to find the truth based on the scientific logic of law from a normative side, studying the application of rules or norms in positive law to find legal rules, legal principles, and doctrines, generate arguments, theories, or new concepts to find solutions to legal issues that arise and answer problems. The results of the study show that there are differences between Indonesia and the United States regarding criminal sanctions for money substitutes in the concept of law enforcement for criminal acts of corruption.